Management control systems in the traditional clannish societies: A case study of a telecommunication company in Somalia - Hared, Bashir Abdisamad (2014)
Both traditional and contemporary perspectives of management control systems (MCS) failed to cope with the socio-cultural settings of the organizations operating in the traditional societies. The evolution of MCS in this socio-cultural context is an emerging research issue that has received less attention in the current MCS research. Therefore, this study attempts to understand, interpret and report the main MCS themes of organizations operating in the traditional societies of less developed countries. Based on the MCS literature, a conceptual framework was developed to better our understanding of the MCS forms that are practiced by the business organizations that are operating in the traditional clannish societies of Somalia. A qualitative case study was adopted to collect the field data from one of the telecommunication companies in Somalia. Similarly, the study uses semi-structured interviews with the executive directors, heads of divisions and some selected customers. To triangulate the data sources, observation and document analyses were employed. The findings of the study show the role of traditional clannish culture on the MCS development in Somalia. The prevalent MCS themes of the studied company include: clannish ownership, paternal leadership, collective responsibility, horizontal relationships, clannish customer recruitment/retention, clan-based selective employment of investors/staff, familial information sharing networks, friendship and personal trust, verbal communication, informal decision making process, centralized control practices, restricted information to specific groups and oral circulation of financial information. These control practices of the telecommunication company in the traditional clannish societies renders formal MCS to become less relevant. Therefore, the traditional clannish norms might play an important role in the emergence of specific MCS forms in the traditional clannish environments like Somalia. The outcome of the study calls for further researches to better our understanding of the MCS evolution, particularly that of the traditional societies in the developing nations